ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MENGGUNAKAN E-MONEY OVO DI KARAWANG (STUDI PADA PENGGUNA OVO DI KARAWANG) - Pamela Octaviana; Abdul Yusuf (Universitas Muhammadiyah Metro Lampung, 2021)
The title of this study is Analysis of factors that influence interest in using OVO e-money in Karawang. This study aims to analyze the factors that influence the interest of OVO e-money users to use OVO e-money. The data used is primary data and analyzed using factor analysis. The sample studied was as many as 100 respondents. In the analysis of interest factors using this there are 5 Variables namely Perception of Usefulness, Perception of Ease, Planned Behavior, Subjective Norms, Perceived Behavior Control and the data was tested using SPSS 16. The results of the research and discussion of the results of the analysis on Interest Factors Using OVO e-money Application. Therefore, the authors can conclude the results of the study, namely: (1) variable of factors using mutual positive influence with interest factors using with the results of 0.224 (2) Indicators in the variables of this study are also positively correlated with values above > 0.5.Keywords: TAM Concept, TPB Concept, Interest in Using, E-Money OVO